2012
DOI: 10.1089/scd.2011.0607
|View full text |Cite
|
Sign up to set email alerts
|

HeliosTranscription Factor Expression Depends onGsx2andDlx1&2Function in Developing Striatal Matrix Neurons

Abstract: Development of the nervous system is finely regulated by consecutive expression of cell-specific transcription factors. Here we show that Helios, a member of the Ikaros transcription factor family, is expressed in ectodermal and neuroectodermal-derived tissues. During embryonic development, Helios is expressed by several brain structures including the lateral ganglionic eminence (LGE, the striatal anlage); the cingulated, insular and retrosplenial cortex; the hippocampus; and the accessory olfactory bulb. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 71 publications
1
39
0
Order By: Relevance
“…See Table 1 for a list of all primary antibodies used in this study. The rabbit polyclonal chicken ovalbumin upstream promoter transcription factor-interacting protein 2 (CTIP2) antibody used in this study has been shown to recognize specifically deep-layer cortical neurons in developing mouse cerebral cortex (Diaz-Alonso et al, 2012;Hong et al, 2013;Chinn et al, 2015;Liu et al, 2015) and the MSNs of the developing mouse striatum (Martin-Ibanez et al, 2012), both of which have been shown to express CTIP2 in many previous studies (Arlotta et al, 2008;Desplats et al, 2008;Leone et al, 2008;Leyva-Diaz and Lopez-Bendito, 2013). Our immunohistochemical analyses in the developing striatum with this antibody showed a staining pattern of CTIP2 consistent with previous descriptions (Arlotta et al, 2008;Desplats et al, 2008;Martin-Ibanez et al, 2012).…”
Section: Antibody Characterizationsupporting
confidence: 86%
“…See Table 1 for a list of all primary antibodies used in this study. The rabbit polyclonal chicken ovalbumin upstream promoter transcription factor-interacting protein 2 (CTIP2) antibody used in this study has been shown to recognize specifically deep-layer cortical neurons in developing mouse cerebral cortex (Diaz-Alonso et al, 2012;Hong et al, 2013;Chinn et al, 2015;Liu et al, 2015) and the MSNs of the developing mouse striatum (Martin-Ibanez et al, 2012), both of which have been shown to express CTIP2 in many previous studies (Arlotta et al, 2008;Desplats et al, 2008;Leone et al, 2008;Leyva-Diaz and Lopez-Bendito, 2013). Our immunohistochemical analyses in the developing striatum with this antibody showed a staining pattern of CTIP2 consistent with previous descriptions (Arlotta et al, 2008;Desplats et al, 2008;Martin-Ibanez et al, 2012).…”
Section: Antibody Characterizationsupporting
confidence: 86%
“…S1" type="url"/>) until P15 peaking at E18.5 (Martín-Ibáñez et al, 2012). He showed preferential expression in D2R-eGFP neurons (mean±s.e.m.…”
Section: Resultsmentioning
confidence: 99%
“…He- expressing cells are derived from radial glial cells, as its expression disappears in Gsx2 knockout mice (Martín-Ibáñez et al, 2012). However, He loss does not compromise the number of the radial glial cell subtypes described elsewhere (Pilz et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The zinc finger transcription factors Ikaros and Helios have also been implicated in striatal neuron development downstream of Gsx2 and Dlx genes (46,47). Moreover, Ikaros has been associated with the differentiation of a subpopulation of Enkexpressing striatopallidial neurons (46,48).…”
Section: Significancementioning
confidence: 99%